1997
DOI: 10.1103/physrevb.55.7831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the photocurrent action spectra of MEH-PPV polymer photodiodes

Abstract: We have measured the photocurrent action spectra of the conjugated polymers poly͓2-methoxy, 5 ethyl ͑2Ј hexyloxy͒ paraphenylenevinylene͔ ͑MEH-PPV͒ and poly͑phenylenevinylene͒ ͑PPV͒ in sandwich cells between indium tin oxide ͑ITO͒ and aluminum electrodes. Under forward bias and illumination through ITO, the photocurrent spectrum is broad and has a maximum at high energy, where the absorption coefficient is greatest ͑the symbatic response͒. Under reverse bias and illumination through ITO, the photocurrent spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(109 citation statements)
references
References 87 publications
4
103
0
2
Order By: Relevance
“…26 The potential for organic photodetectors (OPDs) to achieve filter-less narrowband colour sensing was recognised early in the first homojunctions and linear heterojunctions. 27 However, these devices were limited by the excitonic nature of organic semiconductors that typically exhibit exciton binding energies of order 100s of meV, severely impacting charge generation and hence, transport and external quantum efficiency (EQE). This problem has been largely resolved by employing the bulk heterojunction (BHJ), a blend of two organic semiconductors with different chemical potential energies, the donor and the acceptor, to facilitate charge separation.…”
Section: Organic Semiconductor Photodetectorsmentioning
confidence: 99%
“…26 The potential for organic photodetectors (OPDs) to achieve filter-less narrowband colour sensing was recognised early in the first homojunctions and linear heterojunctions. 27 However, these devices were limited by the excitonic nature of organic semiconductors that typically exhibit exciton binding energies of order 100s of meV, severely impacting charge generation and hence, transport and external quantum efficiency (EQE). This problem has been largely resolved by employing the bulk heterojunction (BHJ), a blend of two organic semiconductors with different chemical potential energies, the donor and the acceptor, to facilitate charge separation.…”
Section: Organic Semiconductor Photodetectorsmentioning
confidence: 99%
“…OPDs utilizing thick junctions have previously been reported 15,22,33,35 . In particular, Armin et al 35 recently described photodiodes with impressive performance metrics for broadband visible, IR-blind light detection using the archetypal bulk heterojunction organic semiconductor donor: acceptor blend of PCDTBT:PC70BM [(poly[N-9 00 -heptadecanyl-2,7-carbazole-alt-5,5-(4 0 ,7 0 -di-2-thienyl-2 0 ,1 0 ,3 0 -benzothiadiazole)]: PC70BM].…”
Section: Resultsmentioning
confidence: 99%
“…Harrison et al 33 have shown that a narrow response can be obtained around the absorption onset of neat MEH-PPV thick photodiodes via enhanced exciton dissociation efficiency at lower energies. In our current work, we introduce the new concept of charge collection narrowing (CCN) in thick bulk heterojunctions to achieve narrowband OPDs.…”
mentioning
confidence: 99%
“…2 reported before; 14,15 the maximum of photocurrent action spectra is located at the photon energy ͑ϳ2.4 eV͒ where the optical absorption is very weak. The spectral response shows a maximum at a photon energy that balances the competing factors of the absorbed light intensity and the position of photocarrier generation with respect to the collecting electrodes.…”
Section: ͓S0003-6951͑98͒04122-9͔mentioning
confidence: 93%